The Impact of Implementing a Carbon Tax on Welfare: Case Study of Indonesia and The Other ASEAN Member Countries - Andrianus, Fery; Handra, Hefrizal; Ayu, Putri; Safitri, Pipin Dwi; Cahyadi, Ria Vinola K. (International Journal of Energy Economics and Policy, 2024)
Green House Gases emitted into the atmosphere over decades cause global warming now. The aim of this research is the impact of implementing the carbon tax on welfare in Indonesia. The research method used is the CGE method using GTAP-E to evaluate energy policy in the economy. GTAP-E consists of 140 countries and 57 sectors combined into forty-two regions and eight sectors. Using carbon tax scenario (simulation 1 is 1.93 USD/ton CO 2, simulation 2 is 3.72 USD/ton CO 2, and simulation 3 is 4.83 USD/ton CO 2). The results of the Indonesian equivalent variation show a negative value. The higher the carbon tax is applied, the greater the decline in welfare. This is also felt by all research countries except the Philippines, Singapore, Thailand, Oceania, OtherSEAsia, East Asia, Argentina, Japan, Poland, Portugal, and Ukraine. The variable of the regional demand, it can be seen that the carbon tax causes Indonesia’s regional income to increase, and Singapore’s income to decrease, while other countries experience no change in income. The primary factor return ratio also shows that the increase in the carbon tax caused a decline in the Land, Unsklab, Sklab, Capital, and Natural Resources sectors. Indonesia’s GDP also shows a decrease if a higher carbon tax is implemented, but other countries have no impact on GDP. The Carbon emissions show that it decreases to Indonesia. So, the implementation of the carbon tax causes a decrease in welfare as seen from the equivalent variation, Primary Return Ratio, and GDP in Indonesia. The government must have an alternative policy if a carbon tax is implemented in Indonesia.